Solving Combined Economic Emission Dispatch Problem with Wind Energy Penetration Using Intelligent Firefly Algorithm - Prabha, A.; Themozhi, G.; Reddy, S.Rama (International Journal of Psychosocial Rehabilitation, 2020)
Electrical power system is the largest man made network. This network connects generating station to consumers. The aim is to satisfy consumers by supplying reliable, quality power supply at economical cost. Major part of the power generation is by coal power plant and they emit pollution in the environment. For social welfare and government rules insists minimization emission from the power plant. The power generating and supply providers have to satisfy both consumer demands as well the environment aspect. These objectives of minimization of generating cost and emission is important and considered in this research work. In practical aspect, when generating cost is minimized it leads to increase in emission. Similarly when emission is minimized the generating cost is increase. Hence a compromise and optimal solution is needs to find for the best operating point to get optimal generating cost and emission. Recent advancement and green power generation of wind energy generation is increasing day by day and included in the power system. This green power generation will further reduce the emission but it depends on the wind velocity hence during the sufficient wind the wind energy is penetrated into the power system and other times the load is fully supplied by the coal power plant. Convention optimization techniques has a drawback to struck in local minimum points in the solution space hence intelligent firefly algorithm is used in this research to find minimum generating cost and minimum emission of the power system. ,